NON-CONVERGENT ORDERING AND DISPLACIVE PHASE TRANSITION IN PIGEONITE: IN SITU HT XRD STUDY - Camara F.; Carpenter M.A.; Domeneghetti M.C.; Tazzoli V. (My University, 2002)
A natural Ca-rich pigeonite (En47Fs43Wo10), free of augite exsolution products, was studied by in situ high-temperature single-crystal X-ray diffraction. The sample, monoclinic P21/c (a=9.719(7) A, b=8.947(9) A, c=5.251(3) A, β=108.49(5), V=433.0(6) A3), was annealed up to 1000 °C to induce a phase transition from P21/c to C2/c symmetry. Complete single-crystal X-ray diffraction data collections were carried out in situ at 650, 750, 850 and 950 °C after the crystal had reached equilibrium for the Fe-Mg intracrystalline exchange reaction at each temperature. The variation, with increasing temperature, of lattice parameters, of intensity of hkl reflections with h + k=2n + 1 (which vanish at high temperature) and of some geometrical parameters from structure refinement, showed that the displacive phase transition P21/c ⇆ C2/c was continuous in character. This contrasts with the first-order character for the HT phase transition in pigeonite containing significantly less calcium.
Keywords: PIGEONITE; IN SITU HT-XRD; PHASE TRANSITION; ORDER-DISORDER